2016
DOI: 10.1186/s40064-016-2261-y
|View full text |Cite
|
Sign up to set email alerts
|

Exploring background risk factors for fatigue crashes involving truck drivers on regional roadway networks: a case control study in Jiangxi and Shaanxi, China

Abstract: BackgroundFatigue driving is a leading cause of traffic fatalities and injuries in China, especially among heavy truck drivers. The present study tried to examine which and how factors within the human-vehicle-roadway-environment system contribute to the occurrence of crashes involving fatigued truck drivers.FindingsTo reduce such risk on the road, a total of 9168 crashes which occurred in Jiangxi and Shaanxi between 2003 and 2014 were selected to measure the effects of potential factors on fatigue related tru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
20
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 33 publications
8
20
3
1
Order By: Relevance
“…In order to describe the created logistic model, the following measures of fit were used (Allison 2014;Awa et al 2016;Chen, Zhang 2016;Chun-Hung 2015;Nagelkerke 1991;Peng et al 2002): , it means that customers do not trust traditional banking, while 1 = Y stands for clients' trust into traditional banking. Respondents' age was marked as categorical variable, which could gain a value of 0 and 1 (0 means that the respondent is 35 years old or under, 1 means that the respondent is above 35).…”
Section: Methodsmentioning
confidence: 99%
“…In order to describe the created logistic model, the following measures of fit were used (Allison 2014;Awa et al 2016;Chen, Zhang 2016;Chun-Hung 2015;Nagelkerke 1991;Peng et al 2002): , it means that customers do not trust traditional banking, while 1 = Y stands for clients' trust into traditional banking. Respondents' age was marked as categorical variable, which could gain a value of 0 and 1 (0 means that the respondent is 35 years old or under, 1 means that the respondent is above 35).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, it has been recorded that malfunction traffic light did not only cause traffic jam in China, but also increased the accident risk [6]. Likewise, inadequate road network and absence of tunnels and bridges also significantly lead toward the occurrence of road accident [31,32]. Inadequate road network in Sri Lanka to cater the increment of car ownership has caused massive traffic jam in the country, which subsequently led to a higher accident involvement rate [32].…”
Section: Road Faultymentioning
confidence: 99%
“…Thirdly, in terms of road geometric design, most accidents have been reported to occur at curve and narrow roads [6,13,17,21,31,33]. Young drivers were reported to be the most involved in road accident at the curve and narrow roads in several countries like Nigeria, China and the US [21,31,33]. Two studies conducted in Pakistan reported that accident usually occurred at hazardous road sections [26,27].…”
Section: Road Faultymentioning
confidence: 99%
See 2 more Smart Citations